Architecting Adaptive Enterprise Intelligence through Secure Cloud Platforms and AI Driven Intelligent Decision Systems (International Journal of Research Publications in Engineering, Technology and Management (IJRPETM), 2026)
The rapid advancement of digital technologies has transformed enterprise operations by enabling organizations to adopt intelligent, data-driven decision-making systems supported by secure cloud computing platforms. Adaptive enterprise intelligence integrates artificial intelligence (AI), machine learning, big data analytics, cloud infrastructure, cybersecurity, and business intelligence to create responsive organizational ecosystems capable of adapting to dynamic market conditions. Secure cloud platforms provide scalable computing resources, real-time data accessibility, and cost-efficient infrastructure, while AI-driven intelligent decision systems facilitate predictive analytics, automation, and strategic planning. This study explores the architecture of adaptive enterprise intelligence by examining the integration of secure cloud technologies with AI-enabled decision support mechanisms. The research investigates the essential architectural components, including cloud security frameworks, data governance, AI algorithms, distributed computing, and enterprise knowledge management. A qualitative research methodology based on secondary data analysis is employed to synthesize findings from scholarly literature, industry reports, and technological frameworks. The study demonstrates that secure cloud environments significantly enhance organizational agility, operational resilience, and innovation capabilities while ensuring confidentiality, integrity, and availability of enterprise data. Furthermore, AI-driven decision systems improve strategic responsiveness through real-time analytics and intelligent automation. The findings contribute to a comprehensive understanding of adaptive enterprise intelligence architecture and provide recommendations for organizations seeking sustainable digital transformation, competitive advantage, and secure intelligent enterprise ecosystems.
Keywords: Adaptive Enterprise Intelligence; Secure Cloud Platforms; Artificial Intelligence; Intelligent Decision Systems; Cloud Computing; Machine Learning; Cybersecurity; Business Intelligence; Data Analytics; Digital Transformation; Enterprise Architecture; Decision Support Systems; Data Governance; Predictive Analytics; Organizational Agility